Hyperuricemia in Children and Adolescents with Autism Spectrum Disorder Treated with Risperidone: The Risk Factors for Metabolic Adverse Effects - Vanwong, Natchaya; Srisawasdi, Pornpen; Ngamsamut, Nattawat; Nuntamool, Nopphadol; Puangpetch, Apichaya; Chamkrachangpada, Bhunnada; Hongkaew, Yaowaluck; Limsila, Penkhae; Kittitharaphan, Wiranpat; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2017)
Background: Atypical antipsychotics have been found to be associated with hyperuricemia. Risperidone, one of the atypical antipsychotics, might be related to the hyperuricemia among autism spectrum disorder (ASD) patients. The aims of this study were to determine the prevalence of hyperuricemia in ASD patients treated with risperidone and to determine associations between serum uric acid levels and risperidone dosage, treatment duration, and metabolic parameters. Methods: 127 children and adolescents with ASD treated with risperidone and 76 age-matched risperidone-naïve patients with ASD were recruited. The clinical data and laboratory data were analyzed. Hyperuricemia was defined as serum uric acid >5.5 mg/dl. Results: Hyperuricemia was present in 44.70% of risperidone-naïve patients with ASD and 57.50% of ASD patients treated with risperidone. The fasting uric acid levels were significantly higher in the risperidone group than in the risperidone-naïve group (5.70 vs. 5.35 mg/dl, P=0.01). The increased uric acid concentrations were significantly associated with adolescent patients treated with risperidone. The higher dose of risperidone and/or the longer treatment time were associated with the increased uric acid levels. Uric acid levels significantly rose with body mass index (BMI), waist circumference (WC), triglyceride (TG) levels, triglycerides to high-density lipoprotein cholesterol ratio (TG/HDL-C), insulin levels, homeostatic model assessment index (HOMA-IR), high-sensitivity CRP (hs-CRP) levels, and leptin levels. Conversely, the levels of HDL-C and adiponectin were negatively correlated with uric acid levels. In multiple regression analysis, there were age, BMI, TG/HDL-C ratio, and adiponectin levels remained significantly associated with uric acid levels. Conclusion: Hyperuricemia may play a role in metabolic adverse effect in children and adolescents with ASDs receiving the high dose and/or the long-term treatment with risperidone.